Gut microbiota as predictors of the occurrence of high on-treatment platelet reactivity in acute ischemic stroke patients - Lou, Zhenzhen; Ouyang, Huiying; Chen, Guixian; Li, Xiaojun; Chen, Haoxuan; Zhan, Yibo; Peng, Lilin; Du, Chenghao; Zheng, Zequan; Wen, Longlong; Xu, Haoyou; Zhao, Min; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction In this study, we aimed to investigate the association between gut microbiota and high on-treatment platelet reactivity (HTPR) in patients with acute ischemic stroke (AIS). Methods We enrolled a total of 48 AIS patients, including 19 HTPR patients and 29 non-high on-treatment platelet reactivity (NHTPR) patients, along with 10 healthy controls. Clinical and laboratory data, as well as stool samples, were collected from all participants. The composition and function of gut microbiota were assessed using 16S rRNA sequencing. Differences in the gut microbiota between the two groups were analyzed, and a diagnostic model based on the gut microbiota was established using random forest model. Results HTPR patients exhibited a decreased microbial richness compared to NHTPR patients. Additionally, the relative abundance of unidentified_Clostridia and Ralstonia was lower in HTPR patients. Significant differences in biological functions, such as toxoplasmosis, were observed between the two groups. The combination of Ralstonia, unidentified-Clostridia, Mailhella, Anaerofustis, and Aggregatibacter showed excellent predictive ability for HTPR occurrence (AUC=0.896). When comparing AIS patients with healthy controls, alterations in the microbiota structure were observed in AIS patients, with imbalances in short-chain fatty acid-producing bacteria and pathogenic bacteria. Significant differences in biological functions, such as oxidative phosphorylation, were noted between the two groups. The combination of Alloprevotella, Terrisporobacter, Streptococcus, Proteus, and unidentified_Bacteria exhibited strong predictive power for AIS occurrence (AUC=0.994). Conclusions This study is the first to uncover the microbial characteristics of HTPR in AIS patients and demonstrate the predictive potential of specific bacterial combinations for HTPR occurrence.